Numerical Evaluation of Delamination on Mode II in Glass Fiber Reinforced Composites - KHOSHRAVAN, M.R.; MONIR VAGHEFI, M. (Engineering Transactions, 2005)
In this paper, delamination of Mode II in a stratified glass fiber-epoxy resin under static loading is investigated. From the results obtained by the finite element method, using the criteria of Irwin-Kies and other theories of elasticity, the strain energy release rate is evaluated. The obtained numerical results are compared with known experimental and theoretical results. Considering local effects, such as fiber bridging in the finite element program, the scatter between experimental and numerical results is evaluated. The specimen is an ENF (End-Notched Flexure) beam and finite element analysis is carried out using the ANSYS software. Paper presented at the 34-th Solids Mechanics Conference, September 2-7, 2002, Zakopane.